2018
DOI: 10.1029/2018gc007966
|View full text |Cite
|
Sign up to set email alerts
|

Extending Global Continuous Geomagnetic Field Reconstructions on Timescales Beyond Human Civilization

Abstract: Study of the late Quaternary geomagnetic field contributes significantly to understanding the origin of millennial‐scale paleomagnetic secular variations, the structure of geomagnetic excursions, and the long‐term shielding by the geomagnetic field. A compilation of paleomagnetic sediment records and archeomagnetic and lava flow data covering the past 100 ka enables reconstruction of the global geomagnetic field on such long‐term scales. We use regularized inversion to build the first global, time‐dependent, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
141
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(156 citation statements)
references
References 94 publications
6
141
0
Order By: Relevance
“…A recently published RPI stack for 10‐40 ka based on high‐deposition‐rate sediments from the Iberian Margin and elsewhere (Figure ) is supported by paleointensity estimates from revised calculation of 10 Be flux in Greenland ice cores (Channell et al, ) using the GICC05 Greenland ice‐core age model (Svensson et al, ). Models and stacks covering the same 0‐ to 40‐ka interval that use RPI data from lower sedimentation rate sequences (e.g., Panovska et al, ) cannot resolve the detail that is revealed by higher sedimentation rate sequences and by 10 Be flux in ice cores.…”
Section: The Geomagnetic Fieldmentioning
confidence: 99%
“…A recently published RPI stack for 10‐40 ka based on high‐deposition‐rate sediments from the Iberian Margin and elsewhere (Figure ) is supported by paleointensity estimates from revised calculation of 10 Be flux in Greenland ice cores (Channell et al, ) using the GICC05 Greenland ice‐core age model (Svensson et al, ). Models and stacks covering the same 0‐ to 40‐ka interval that use RPI data from lower sedimentation rate sequences (e.g., Panovska et al, ) cannot resolve the detail that is revealed by higher sedimentation rate sequences and by 10 Be flux in ice cores.…”
Section: The Geomagnetic Fieldmentioning
confidence: 99%
“…Summary diagram of geomagnetic field models, paleointensity stacks, and dipole moment reconstructions covering timescales from the Holocene to 5 Ma. References: OH1992 (Ohno & Hamano, ), OH1993 (Ohno & Hamano, ), CALS10k.1b (Korte et al, ), CALS10k.2 (Constable et al, ), HFMx, HFM.OL1 (Panovska et al, ), HFM.OL1.A1 (Constable et al, ), YOS2000 (Yang et al, ), SHA.DIF.14k (Pavón‐Carrasco et al, ), MS1982 (McElhinny & Senanayake, ), GEOMAGIA VADM (Knudsen et al, ), C2018‐Overall stack (Channell et al, ), NAPIS‐75 (Laj et al, ), IMOLE (Leonhardt et al, ), LSMOD.1 (Brown et al, ), LSMOD.2 (Korte, Brown, Panovska, & Wardinski, ), GLOPIS‐75 (Laj et al, ), SAPIS (Stoner et al, ), GGF100k (Panovska, Constable, & Korte, ), sint‐200 (Guyodo & Valet, ), IMIBE (Lanci et al, ), NOPAPIS‐250 (Yamamoto et al, ), SAS‐300 (Hofmann & Fabian, ), SASC‐300 (Hofmann & Fabian, ), RADM (Ziegler & Constable, ), S1999 (Shao et al, ), IMMAB4 (Leonhardt & Fabian, ), IT2008 (Ingham & Turner, ), sint‐800 (Guyodo & Valet, ), PISO‐1500 (Channell et al, ), HINAPIS‐1500 (Xuan et al, ), M1995 (Mazaud, ), sint‐2000 (Valet et al, ), PADM2M (Ziegler et al, ), EPAPIS‐3Ma (Yamazaki & Oda, ), NARPI‐2200 (Channell et al, ), SK1990 (Schneider & Kent, ), GK1993 (Gubbins & Kelly, ), MM1977 (Merrill & McElhinny, ), LN1, LR1 (Johnson & Constable, ), MMM1996 (McElhinny et al, ), LSN1, LSR1 (Johnson & Constable, ), KG1997 (Kelly & Gubbins, ), CC1998 (Carlut & Courtillot, ), MF‐1, MF‐2, MF‐3 (Shao et al, ), LN3, LN3‐SC (Cromwell et al, ).…”
Section: Data Synthesis Results: Stacks and Sh Models From 10 Kyr To mentioning
confidence: 99%
“…Roberts () discussed the strengths and limitations of u‐channels and suggested strategies for mitigating the limitations of these measurements. In field modeling, however, it is preferable to take account of the instrument convolution in the forward modeling thereby directly predicting the smoothed observations (Panovska et al, ).…”
Section: Data On the Past Geomagnetic Fieldmentioning
confidence: 99%
See 2 more Smart Citations